Mathematical Formulas for Economists - Luderer, Bernd; Nollau, Volker; Vetters, Klaus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The present collection of formulas has been composed for students of economics or management science at universities, colleges and trade schools. It contains basic knowledge in mathematics, financial mathematics and statistics in a compact and clearly arranged form. This volume is meant to be a reference work to be used by students of undergraduate courses together with a textbook, and by researchers in need of exact statements of mathematical results. People dealing with practical or applied problems will also find this collection to be an efficient and easy-to-use work of reference. This carefully revised and enlarged edition also presents methods of rank statistics and the analysis of variance (ANOVA) and covariance.
Mathematical Symbols and Constants -- Sets and Propositions -- Number Systems and Their Arithmetic -- Combinatorial Analysis -- Sequences and Series -- Mathematics of Finance -- Functions of one Independent Variable -- Functions of one Variable: Differential Calculus -- Functions of one Variable: Integral Calculus -- Differential Equations -- Difference Equations -- Differential Calculus for Functions of Several Variables -- Linear Algebra -- Linear Programming. Transportation Problem -- Descriptive Statistics -- Calculus of Probability -- Inductive Statistics -- Tables.
Keywords: Economics; Mathematics; Economics, Mathematical; Economics/Management Science; Game Theory/Mathematical Methods; Operations Research/Decision Theory; Game Theory, Economics, Social and Behav. Sciences